Interpreting the Existence of Dewala and Ina Leta as the Center of the Tounwawan People's Life Narrative in Southwest Maluku, Indonesia - Koritelu, Paulus; Steijlen, Fridus (JSW (Jurnal Sosiologi Walisongo), 2024)
Dewala and Ina Leta mean stone walls and mother village, respectively. These are monuments that symbolize “the beginning of life” narrative of the Tounwawan people of Moa Islands, Maluku, Indonesia. This first settlement narrative has become the collective memory of the Tounwawan community. It preserves their socio-cultural identity and helps them understand their roles and positions, perceiving themselves and others living together in the same environment. The research method used in this study is a qualitative approach with a phenomenological type. The data were collected through in-depth interviews, observations, and documentation. The research results show that the Tounwawan people preserve Dewala and Ina Leta to symbolize the origin of their lives, elements of collective memory that can endure the test of time. The findings also show that the Tounwawan people maintain their intersubjective relations, which allows the noble values represented by these two monuments to be passed down as interpretable knowledge and experiences for the following generation.